2022
DOI: 10.21203/rs.3.rs-1701960/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatiotemporal differences and influencing factors of high-quality utilization of land resources in the Yellow River Basin of China

Abstract: High-quality utilization of land resources (HULR) is related to security of land ecosystem and sustainable development of socio-economy. To promote the HULR, we explored the spatiotemporal differences and influencing factors of HULR in the Yellow River Basin (an important ecological barrier in China) by using entropy method, spatial panel regression model, and geographically and temporally weighted regression model. We found that the HULR values were 0.22 to 0.28 from 2008 to 2019, showing an increasing trend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The index system for assessing the degree of urbanization has been constructed using four dimensions: population, economy, society, and ecology. This framework is grounded in theoretical discussions regarding the essence of new urbanization [3,11,36] and references the "evaluation index system for in situ urbanization" [37]. For the index system for evaluating land use efficiency, input-related indicators are selected from capital input, labor input, and land input, while output-related indicators are chosen from economic benefits, social benefits, and environmental benefits [36,38,39].…”
Section: The Index System and Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…The index system for assessing the degree of urbanization has been constructed using four dimensions: population, economy, society, and ecology. This framework is grounded in theoretical discussions regarding the essence of new urbanization [3,11,36] and references the "evaluation index system for in situ urbanization" [37]. For the index system for evaluating land use efficiency, input-related indicators are selected from capital input, labor input, and land input, while output-related indicators are chosen from economic benefits, social benefits, and environmental benefits [36,38,39].…”
Section: The Index System and Data Sourcesmentioning
confidence: 99%
“…Researchers, both in China and internationally, have conducted comprehensive studies of the interplay between urbanization and land use, and all have underscored the inherent interconnection between urbanization and land utilization [8,9]. This relationship has gradually become more complex with the development of urbanization [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, these studies indicate that it will be extremely challenging to implement a low-carbon economic development model in the short term [30]. As far as the YRB is concerned, scholars have found that the overall pattern of carbon emissions in the YRB is "high in the east and low in the west", the carbon sink pattern is "high in the west and low in the east" [31], and the intensity of carbon emissions presents a spatial distribution pattern with coexistence of "agglomeration" and "differentiation" [32]. The carbon emissions efficiency gap presents a W-shaped evolution trend, as well as a stepped distribution pattern of "upstream-midstream-downstream" [33].…”
Section: Introductionmentioning
confidence: 99%
“…In the processes of protection and utilization, a problem may arise in that the number and scale of assets remain stable while the actual value decreases [30]. It can be seen from a review of the existing literature that the approaches to protection and utilization of natural resource assets are mostly dominated by single elements [31][32][33][34][35]; however, research on the protection and utilization of natural resource assets in the sense of mountains, rivers, forests, farmlands, lakes, and grasslands is almost nonexistent, and there is a lack of established practices and mechanisms for the protection and utilization of natural resource assets falling into these key types. The existing studies on the protection and utilization of each resource type also suffer from different levels of progress, inconsistent structure, and different indexing systems, and thus cannot be directly applied to the unified management of natural resources owned by the general population.…”
Section: Introductionmentioning
confidence: 99%